Navigating complexities in leadership : moving toward critical hope - Guthrie, Kathy L.; Priest, Kerry L. (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"Navigating Complexities in Leadership: Moving Towards Critical Hope emerged in response to the confluence of complexities experienced by leadership educators and practitioners amidst global pandemics. It is a guide for those seeking to learn through critical perspecitves, and seek more agile, responsive tools for navigating complexity, change, and disruption. The audience for the book ranges from new and entry-level leadership educators to senior scholars in higher education. This book frames leadership learning and development as a process of adaptive action in complex systems. It brings to light patterns of complexity in current times through the lens of educators and practitioners in higher education. Readers are invited to actively engage with the text from an inquiry stance. Through curiosity, shared exploration, self-reflection we hope readers will discover patterns and insight that resonate and challenge their own experiences, find energy to engage the complexities being faced, and build adaptive capacity to live, work, teach, and lead in critical hope and possibility. The book concludes with questions and considerations that allow educators and practitioners to reflect on their own roles and contexts and move towards critical hope in navigating the complexities we will continue to face"-- Provided by publisher.
Keywords: Leadership -- Philosophy.; Leadership -- Study and teaching (Higher); Educational leadership.; Educational change.; Education -- Leadership.; Educational administration and organization.; Educational strategies and policy.; elektronické knihy; electronic books